Proactivity, mindsets and the development of students' entrepreneurial self-efficacy: behavioural skills as the catalyst. Issue 5 (20th October 2022) - Bi, Qingqing C.; Collins, Jamie
ABSTRACT: With the promotion of entrepreneurship and innovation in higher education, university students have become the emerging entrepreneurial subjects worldwide. Developing students' entrepreneurial self-efficacy can increase their entrepreneurial intentions and the likelihood to engage in student entrepreneurship. Recent studies have found that students' implicit mindsets (i.e. growth mindsets and fixed mindsets) have significant impact on their entrepreneurial self-efficacy. Building upon these studies, we argue that not only students' traits (i.e. proactivity) and mindsets influence the development of their entrepreneurial self-efficacy, students' behavioural skills relevant to entrepreneurship (i.e. entrepreneurial behaviours) function as the catalyst in the web of relationships. To test the hypothesis, we surveyed 154 students in a public university of New Zealand. The results showed that university students' entrepreneurial behaviours fully mediated the relationship between their fixed mindsets and entrepreneurial self-efficacy, and partially mediated the relationship between proactivity and entrepreneurial self-efficacy. The findings confirm the importance of both traits and mindsets in the development of students' entrepreneurial self-efficacy, and also identify the bridging role of behavioural skills. This study contributes to the implicit theory approach for understanding entrepreneurial self-efficacy and highlights the importance of practising behaviour skills to foster students' entrepreneurial self-efficacy.